Optimal and fair prizing in sequential round-robin tournaments: Experimental evidence - Arne Lauber; Christoph March; Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
We report results from the first experimental study of round-robin tournaments. In our experiment, we investigate how the prize structure affects the intensity, fairness, and dynamic behavior in sequential round-robin tournaments with three players. We compare tournaments with a second prize equal to either 0%, 50%, or 100% of the first prize. While theory predicts the 50%-treatment to be most intense, we find that aggregate effort is highest in the 0%-treatment. In contrast, our evidence supports the predictions that the 50%-treatment is fairest (though not perfectly fair), whereas the late mover is advantaged in the 100%-treatment and disadvantaged in the 0%-treatment. Also in line with the theory, we identify a strategic (reverse) momentum: after winning the first match, a player increases (decreases) effort in the second match of the 0%-treatment (100%-treatment). Additional findings suggest that dynamic behavior is also subject to a psychological momentum.
Keywords: C72; C91; D72; Z20; 330; Sequential Round-Robin Tournament; All-pay Auction; Fairness; Intensity; Strategic Momentum; Experiment